Contemporary Circumstances of Companion Animals in China - Pu, Songjie (Transactions on Environment, Energy and Earth Sciences, 2024)
In China, the implementation of animal welfare in the legal system has been relatively lacking when compared to other nations. As the existing flaws and the lack of enforcement of such laws condone many instances of animal cruelty in China’s society, animal welfare and protection have been a topic of growing discussion both in the society and in the academic world of China. However, while most literature focuses on the general welfare of more noticeable animals like wildlife and livestock animals, the abuse, abandonment, and mistreatment of companion animals have been receiving less attention regarding their unfortunate circumstances in China’s society. With a lens on the topic of companion animals, then, this paper aims to uncover the cases of animal cruelty in China and point out the loopholes in relevant laws. This will be done through a combination of a dive into literature in this field as well as statistics, case studies, and government policies. Furthermore, this paper will go on to explain the difficulties of establishing companion animal welfare laws in relation to the Chinese legal system, society, and cultural context, and hence offer suggestions about how companion animal welfare can be achieved.